ANALYSIS OF THE EFFECT OF JOB TRAINING, SELF EFFICACY, AND INNOVATIVE WORK BEHAVIOR ON THE PERFORMANCE OF EMPLOYEES OF BALAI BESAR HANDICRAFT AND BATIK IN YOGYAKARTA - Anisa Permata Hastiti; Didik Subiyanto; Selamet Hartanto (UIN Raden Mas Said Surakarta, 2023)
This study aims to explore a number of important aspects in the context of employee performance at the Center for Handicrafts and Batik in Yogyakarta. First, the study intends to identify whether job training has a positive influence on employee performance. Second, the study aims to assess self-efficacy may contribute positively to improve employee performance. Finally, the study also purposes to determine whether innovative work behaviors have a positive impact on employee performance in the institution. The methodology in this study was quantitative research by using questionnaire instruments to collect data. The sample used in this study consisted of 50 employees from Balai Besar Handicraft and Batik of Yogyakarta. Data analysis was carried out by using various statistical techniques allowing researchers to evaluate causal relationships between the variables studied. The results of the analysis show interesting findings. First, there is evidence to suggest that job training and self-efficacy do not have a significant positive effect on employee performance. This finding invites questions related to other factors that might affect employee performance at the Yogyakarta Handicraft and Batik. On the other hand, the results of the study also show that innovative work behavior has a positive and significant influence on employee performance at Balai Besar Handicraft and Batik. These findings highlight the importance of promoting and supporting innovation in this organizational context to improve employee performance.